Literary Devices in Film Adaptations: A Multimodal Discourse Analysis of The Great Gatsby - Xin Hui Lee; Chandran Gheeta (Sociometry Journal of Social Science, Art and Humanity, 2021)
Multimodal discourse analysis (MDA) is a framework used to analyse a subject by drawing meanings from various semiotic modes such as visuals and audio. Studies have been done to validate the applicability of MDA in advertisements, textbook images, and even website designs. Adding to the validity of MDA, this study adopts the framework to analyze literary devices in films, filling the gap present in previous MDA in films where they focused on character relationship and overall meaning. With the development of various other ways to tell a story other than plain text, this study attempts to analyze literary devices that are found in a literature’s filmic counterparts. Metaphors, symbolism, and allegories that are found in the book The Great Gatsby will be analysed in its 2013 film adaptation to compare and contrast the differences in its way of presentation using Kress and van Leeuwen’s Grammar of Visual Design. Findings suggest that the adopted framework is applicable in analysing literary devices present in the film adaptation of The Great Gatsby as the effective use of visuals allows viewers to better understand the literary devices that were used in the original book. This finding provides additional support for the validity of MDA in film analysis, as well as bridges the relationship between film and literature; thus broadening the prospects of using film as a tool to enhance the effectiveness of literature comprehension and teaching.